Investigation of heavy metal analysis in wastewater samples around the Industrial Area of Gajulamandyam, Tirupati, A.P. - et al., Katepogu. Raju (International Journal of Advanced Science and Technology, 2019)
The present study deals with the characterization of industrial effluents released from various points of gujulamandyam industrial areas and the  distribution of heavy metals in soils are enter into the soil body to disturb the soil biocommunities which are essential for the supporting of the plant growth. The excess amount of HM’s toxicants would leads to reduces the plant growth and ultimately disturb the plant ecosystem. Apart from this, accumulation of heavy metals in nearby soil and vegetation system irrigated with effluent-contaminated water is also the subject of this study. Physico-chemical analysis of effluent reveals that the concentration of total suspended solids (TSS), total hardness (TH), iron (Fe2+), and oil and grease are greater than the IS (1981) norms for discharge of water into inland water body. The soil along the sides of the effluent channel also shows higher concentration of heavy metals than the background soil. The enrichment of the heavy metals are in the order of Chromium (Cr) ,Iron (Fe),Manganese (Mn),Zinc (Zn),Copper (Cu),Cadmium (Cd). The effluent as well as contaminated water is extensively used for irrigation for growing vegetables like tomato (Lycopersicon esculatum) in the surrounding areas. Heavy metal accumulation in this agricultural soil are in the sequence of Cr, Fe, Mn, Zn, Cu and Cd. More or less similar type of accumulation pattern are also found in tomato plants except Fe and Zn exceeding Cr and Mn. Transfer Factor of heavy metals from soil to tomato plants (TFS) shows average value of ≤ 1, suggesting less uptake of heavy metals from soil. Among the plant parts studied, fruit shows least accumulation. Although tomato plants show some phenotypic changes, the survival of tomato plants as well as least accumulation of metals in fruit reveals their tolerance to heavy metals. Therefore it may be suggested that this plant can be grown successfully in the heavy metal contaminated soil. Further research work on in situ toxicity test will be necessary in order to identify the most resistive variety on this particular type of contaminated site.